2021
DOI: 10.1017/wet.2021.73
|View full text |Cite
|
Sign up to set email alerts
|

Resistance in smallflower umbrella sedge (Cyperus difformis) to an acetolactate synthase–inhibiting herbicide in rice: first case in India

Abstract: Smallflower umbrella sedge is one of the problematic weeds in direct-seeded rice in India. Bispyribac-sodium (acetolactate synthase-inhibiting herbicide) is a commonly used in rice, but recently growers have reported lack of smallflower umbrella sedge control with this herbicide. An extensive survey was carried out in two rice growing states, Chhattisgarh and Kerala, where 53 putative bispyribac-sodium resistant (BR) biotypes were collected. Studies were conducted to confirm resistance to bispyribac-sodium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The sole reliance on these practices have resulted in the rapid evolution of imidazolinone-resistant weedy rice, problem of gene flow and accelerated development of resistance in other weed species (Kumar et al 2008;Avila et al 2021). Further, matter of concern is that first case of herbicide resistance in Cyperus difformis L. against bispyribac-sodium (ALS inhibitor) in India (Choudhary et al 2021) was reported recently having the similar mode of action. Nevertheless, comprehensive studies are needed regarding the comparative saving of irrigation water in direct seeded rice keeping in view the farmers' practice of early seeding during the peak evapotranspirative demand in summers and consequent frequent irrigations.…”
Section: Tillage and Residue Management (Crop Establishment)mentioning
confidence: 99%
See 1 more Smart Citation
“…The sole reliance on these practices have resulted in the rapid evolution of imidazolinone-resistant weedy rice, problem of gene flow and accelerated development of resistance in other weed species (Kumar et al 2008;Avila et al 2021). Further, matter of concern is that first case of herbicide resistance in Cyperus difformis L. against bispyribac-sodium (ALS inhibitor) in India (Choudhary et al 2021) was reported recently having the similar mode of action. Nevertheless, comprehensive studies are needed regarding the comparative saving of irrigation water in direct seeded rice keeping in view the farmers' practice of early seeding during the peak evapotranspirative demand in summers and consequent frequent irrigations.…”
Section: Tillage and Residue Management (Crop Establishment)mentioning
confidence: 99%
“…The continuous cultivation of rice-wheat system along with faulty spray techniques have resulted in accelerated herbicide resistance in wheat associated weeds such as Phalaris minor and Rumex dentatus (Chhokar et al 2018). Recently in rice also, first case of herbicide resistance in Cyperus difformis L. against bispyribac-sodium was reported in India (Choudhary et al 2021). The effective dose of bispyribac-sodium required to control 50% of plants was found 19-96 g ha −1 as compared to 10 g ha −1 for susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…However, ALS-resistant barnyardgrass has not yet been confirmed in India. Recently, bispyribac-sodium resistance in another predominant weed, smallflower umbrella sedge ( Cyperus difformis ), has been reported in rice fields in India (Choudhary et al 2021). Hence it is possible that barnyardgrass has developed resistance to the herbicide.…”
Section: Introductionmentioning
confidence: 99%